2014
DOI: 10.1002/path.4344
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next‐generation sequencing of cancer genes dissects the molecular profiles of intraductal papillary neoplasms of the pancreas

Abstract: Intraductal neoplasms are important precursors to invasive pancreatic cancer and an opportunity to detect and treat pancreatic neoplasia before an invasive carcinoma develops. The diagnostic evaluation of these lesions is challenging as diagnostic imaging and cytological sampling do not provide accurate information on lesion classification, the grade of dysplasia or the presence of invasion. Moreover, the molecular driver gene mutations of these precursor lesions have yet to be fully characterized. Fifty-two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
191
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(200 citation statements)
references
References 38 publications
7
191
2
Order By: Relevance
“…GNAS mutations are unique to IPMN, and activation of G-protein signaling may play a crucial role in IPMN progression. Amato et al [49] reported an even higher frequency of GNAS mutation in IPMN (38/48; 79%) using next-generation sequencing. The second most common mutation was KRAS , found in 50% of IPMN, and the third most common was RNF43 , found in 14%.…”
Section: Molecular and Genetic Investigationsmentioning
confidence: 99%
“…GNAS mutations are unique to IPMN, and activation of G-protein signaling may play a crucial role in IPMN progression. Amato et al [49] reported an even higher frequency of GNAS mutation in IPMN (38/48; 79%) using next-generation sequencing. The second most common mutation was KRAS , found in 50% of IPMN, and the third most common was RNF43 , found in 14%.…”
Section: Molecular and Genetic Investigationsmentioning
confidence: 99%
“…Amato et al [23] used next-generation targeted sequencing to find the most important mutations in IPMNs. They identified GNAS (79%), KRAS (50%), RNF43 (14%), TP53 (10%) and BRAF (6%) as the most important mutations.…”
Section: Molecular Markersmentioning
confidence: 99%
“…None of the gastric- or oncocytic-type IPMNs or ITPNs show such mutations, and there is always an association with a GNAS and/or a KRAS mutation. One deletion in exon 2, one insertion in exon 3 and one insertion in exon 7, two missense variants in exons 5 and 9 and one nonsense mutation in exon 9 are found (table 2) [23]. …”
Section: Molecular Markersmentioning
confidence: 99%
See 2 more Smart Citations